Adoecimento docente no Ensino Superior na perspectiva da Psicologia Histórico-Cultural - Dias, Alcione Ribeiro (2021)
The object of investigation of this research is the illness of professors in higher education. We seek to elucidate this process from the perspective of the development of the human psyche, proposed by Cultural-historical Psychology. We seek to systematize principles about the development of the psyche, understanding the structural and functional dimensions to which culturally formed complex behaviors are linked, and correlate them with illness of professors. The research was developed at the Federal University of Mato Grosso do Sul (UFMS) and the investigation method is based on historical-dialectical materialism. The methodological strategies were constituted in four phases: (1) study of the leave data of professors at the Federal University of Mato Grosso do Sul (UFMS) from 2005 to 2019; (2) questionnaires answered by professors from the Human Sciences Area – Campo Grande; (3) individual interviews with professors from the same area; and (4) group research meeting structured with psychodramatic pedagogy, carried out with professors from the Human Sciences Area of Campo Grande and Corumbá. We describe the data and weave explanations about the illness of professors in higher education from axes of analysis relevant to Cultural-historical Psychology, obtaining the following results: (1) In the first phase, the analyzes were carried out through the prism of historicity - the studies indicated growing illness in this 15-year period. The average of 3,775 days of absence, in the first two years, rose to the average level of 9,500 days in the last three years. The main causes are mental and behavioral disorders (CID: F31-F32-F33-F34), neoplasms and musculoskeletal diseases. (2) We analyzed nineteen questionnaires from the perspective of activity, identifying meaning-generating motives and stimuli motives – the professors highlighted in their activity the function of teaching and guiding research, maintaining the purpose in the student's development. Administrative activities and data entry into control systems are actions that do not generate sense. The stimuli reasons that please are: academic autonomy, adequate physical space and nature of the work (teaching, research and extension). Those that dislike are deficient technological structure and relationships with peers (competitiveness) and bosses (arbitrary). Symptoms of mood disorders and musculoskeletal disorders are confirmed in this group, but the highest incidence is in endocrine disorders. Most are satisfied with the teaching activity and do not want to change their profession. Hostile climate, overwork and precarious conditions are factors that generate dissatisfaction. (3) In the interviews, bringing the unique reality of nine professors, we carried out the analyzes based on the production environment and personality axes. In each unique experience, a state of illness or health maintenance is established, due to adjustments in psychic processes and coping actions in the context of social relations. (4) In the research meeting carried out with three groups, nine subjects - we obtained the affective and cognitive resonances of the professors in view of the research data composed in the previous phases; the analysis was based on aspects of the constitution of consciousness, through the processes of thought, affection, and volitional action in reality. In short, we can infer the possibility that the healthy development of the higher education professors’ psyche is being led by the path of illness, due to rupture or non-consolidation of systemic units: (a) activity and awareness and (b) imagination, thought and affects. Keywords: Illness of professors. Psychic development. Cultural-historical Psychology. Psychodramatic Pedagogy. Higher education.